2011
DOI: 10.17221/16/2010-pps
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to fungicides in the isolates of Phytophthora infestans (Mont.) de Bary in the Czech Republic from 2003 to 2008

Abstract: Mazáková J., Zouhar M., Ryšánek P., Táborský V., Hausvater E., Doležal P. In the growing seasons from 2003 to 2008, 547 isolates of Phytophthora infestans from five regions in the Czech Republic were collected and examined for their sensitivity to the active ingredients (metalaxyl, dimethomorph and propamocarb-HCl) of frequently used fungicides. The response of the isolates to each of these substances was examined using the in vitro amended-agar method; in 352 of these isolates, the sensitivity to metalaxyl wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…It is clear from this study that isolates sensitive to metalaxyl prevailed in the population, as also observed in Moscow and other Russian populations of P. infestans [ 21 ]. These findings corroborate results from other studies from Estonia [ 27 ], Latvia [ 25 ], Poland [ 62 , 97 ], Lithuania [ 93 ], the Czech Republic [ 98 ], and Nordic countries [ 96 ]. However, the predominance of metalaxyl-resistant strains has been reported in several European populations, such as the Republic of Ireland, Northern Ireland, France, and Cyprus [ 74 , 99 , 100 , 101 ], which is mainly due to the spread of the mefenoxam-insensitive genotype EU_13_A2.…”
Section: Discussionsupporting
confidence: 91%
“…It is clear from this study that isolates sensitive to metalaxyl prevailed in the population, as also observed in Moscow and other Russian populations of P. infestans [ 21 ]. These findings corroborate results from other studies from Estonia [ 27 ], Latvia [ 25 ], Poland [ 62 , 97 ], Lithuania [ 93 ], the Czech Republic [ 98 ], and Nordic countries [ 96 ]. However, the predominance of metalaxyl-resistant strains has been reported in several European populations, such as the Republic of Ireland, Northern Ireland, France, and Cyprus [ 74 , 99 , 100 , 101 ], which is mainly due to the spread of the mefenoxam-insensitive genotype EU_13_A2.…”
Section: Discussionsupporting
confidence: 91%
“…The majority (72%) of isolates in this study were sensitive to metalaxyl. In the Czech Republic the majority of P. infestans isolates are sensitive to metalaxyl (95% of isolates collected in 2003–2008;Mazáková et al ., ). In Estonia 78·8% of isolates were sensitive to metalaxyl in 2007, although in 2005 only 15·2% were sensitive (Runno‐Paurson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…and other species of oomycetes [37]. Among these, metalaxyl, a phenylamide compound acts by inhibiting RNA polymerisation within the synthesis of ribosomal RNA and results in the inhibition of mycelial growth, haustorium formation and sporulation [38].…”
Section: Discussionmentioning
confidence: 99%